Structure, Attributive and Bacterial Effectiveness Studies for Complexes, Co(II), Hg(II), Ni(II), Cu(II) and Mn(II) with Ligand kind (N2O2) - Al- shemary, Rehab K.; Ghanim, Faeza H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Binuclear copper, nickel, cobalt, manganese and mercury complexes of the Schiff base H2L (C40H28N2O4) obtained by condensation of 2-benzoyl benzoic acid with benzidine. The Schiff base and their complexes have been subjected to[ FT-IR, elemental analysis ,UV-Vis, 1H and 13C NMR ] spectral studies, molar conductivity, magnetic moment and HPLC measurements. All the complexes showed tetrahedral geometries with the general structure [M2(L)2]. Generality of the synthesized components offer antibacterial efficiency to (Staphylococcu saureus), (Escherichia coli),(Bacillus subtilis) and(Pseudomonas aeruginosa).